2021
DOI: 10.1111/tbed.14266
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus in slaughtered dogs for meat consumption in Ghana: A potential risk for rabies transmission

Abstract: Dog‐mediated rabies is responsible for approximately 60,000 human deaths annually worldwide. Although dog slaughter for human consumption and its potential risk for rabies transmission has been reported, mainly in some parts of Western Africa and South‐East Asia, more information on this and factors that influence dog meat consumption is required for a better understanding from places like Ghana where the practice is common. We tested 144 brain tissues from apparently healthy dogs slaughtered for human consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
9
1
Order By: Relevance
“…Dog meat consumption as a delicacy is popular among several tribes in western Africa, particularly in Ghana [ 47 ] and Nigeria [ 48 ], which increases the risk of people contracting rabies. In a similar vein, research in Nigeria found rabies antigens in the brain of dogs slaughtered for human consumption [ 46 ]. The belief of being protected from rabies and evil spirits, the medicinal value, and the taste of its meat all contribute to the consumption of dog meat.…”
Section: Socio-economic Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Dog meat consumption as a delicacy is popular among several tribes in western Africa, particularly in Ghana [ 47 ] and Nigeria [ 48 ], which increases the risk of people contracting rabies. In a similar vein, research in Nigeria found rabies antigens in the brain of dogs slaughtered for human consumption [ 46 ]. The belief of being protected from rabies and evil spirits, the medicinal value, and the taste of its meat all contribute to the consumption of dog meat.…”
Section: Socio-economic Factorsmentioning
confidence: 97%
“…The spread of rabies and the effect of dog slaughter, handling, and ingestion are poorly known. Nonetheless, while not being present in meat or blood, exposure to cuts and wounds during slaughter and canine meat processing to saliva or brain tissues may represent a high danger [ 46 ]. Dog meat consumption as a delicacy is popular among several tribes in western Africa, particularly in Ghana [ 47 ] and Nigeria [ 48 ], which increases the risk of people contracting rabies.…”
Section: Socio-economic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on rabies in Ghana. These include epidemiology and control measures (Addy, 1985; Alonge & Abu, 1984; Belcher et al., 1976; Lopes et al., 2018); surveillance systems (Afakye et al., 2016; Guri et al., 2020); human rabies outbreaks (Amoako et al., 2021; Apanga et al., 2016; Dsane‐Aidoo et al., 2022; Laryea et al., 2017; Punguyire et al., 2017); dog bites and rabies (Abuh et al., 2017; Addai & Nuertey, 2018; Adomako et al., 2018; Dsane‐Aidoo et al., 2022; Eliezer, 2016; Kenu et al., 2018; Korash & Ameme, 2017; Punguyire et al., 2017, 2020); dog population structure (Tasiame et al., 2019); dog‐associated pig rabies (Tasiame et al., 2016); rabies virus in dogs slaughtered for meat consumption (Tasiame et al., 2021); knowledge, attitudes, perceptions, practices and beliefs (Awuni et al., 2019; Tettey, 1998; Turkson & Wi‐Afedzi, 2020; Vetsi et al., 2021) and lineage of rabies virus in Ghana (Hayman et al., 2011). However, no studies have reported on the space–time pattern of the disease countrywide on a national level.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, T. gondii infection in dogs can be an indicator for the level of environmental contamination for humans ( Meireles et al., 2004 ). Additionally, because dog meat serves as food for humans in some regions ( Cui and Wang, 2001 ; Chevalier et al., 2021 ; Tasiame et al., 2021 ), consumption of undercooked dog meat containing T. gondii cysts also poses a health risk.…”
Section: Introductionmentioning
confidence: 99%